Assessing post-game emotions in soccer teams: The role of distinct emotional dynamics - Rumbold, J. L.; Newman, J. A.; Foster, D.; Rhind, D. J. A.; Phoenix, J.; Hickey, L. (European Journal of Sport Science, 2022)
This study examined the relationships between team (n = 10) and player post-game emotions following two consecutive games. In addition, the relationship between emotional contagion susceptibility and player post-game emotions was assessed. Applying an experience sampling methodology, male amateur and semi-professional soccer players (N = 114, Mage = 25.46 years, SD = 9.24) completed a sport emotion questionnaire shortly after the conclusion of two competitive games. Participants also completed a dispositional emotional contagion questionnaire prior to post-game data collection. Multilevel regressions revealed that teams` collective post-game emotions were strongly associated with players` post-game emotions, after accounting for within- (e.g. time, game outcome) and between-person (e.g. formal leaders, emotional contagion susceptibility) differences. In addition, partial support was found to indicate that emotional contagion susceptibility was associated with players` post-game emotions. In this context of soccer, the findings suggest that collective emotions following a game are more indicative of individual players` emotions than an individual`s general tendency to mimic the emotions of others. From an applied perspective, the findings demonstrate the importance of coaches and players being mindful of the team`s emotional climate after a game and the impact it may have on players, especially when that climate is negative.